2020
DOI: 10.1051/0004-6361/202038239
|View full text |Cite
|
Sign up to set email alerts
|

Binary star sequence in the outskirts of the disrupting Galactic open cluster UBC 274

Abstract: We report the identification of a numerous binary star population in the recently discovered ∼3 Gyr old open cluster UBC 274. It becomes visible when the cluster color-magnitude diagram is corrected by differential reddening and spans mass ratio (q) values from 0.5 up to 1.0. Its stellar density radial profile and cumulative distribution as a function of the distance from the cluster center reveal that it extends out to the observed boundaries of the tidal tails of the cluste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
7
2
Order By: Relevance
“…Of the 75 high-confidence clusters recently discovered by Liu & Pang (2019), 35 are present in the latest catalogue from Cantat-Gaudin et al ( 2020), and we provide an RV for most of them. For instance, we provide the mean RV of UBC 274 (also reported as LP 5), a recently discovered disrupting OC (Castro-Ginard et al 2020;Piatti 2020), based on 18 members observed with RAVE, GALAH, and Gaia RVS (Fig. 3).…”
Section: Mean Rvsmentioning
confidence: 99%
“…Of the 75 high-confidence clusters recently discovered by Liu & Pang (2019), 35 are present in the latest catalogue from Cantat-Gaudin et al ( 2020), and we provide an RV for most of them. For instance, we provide the mean RV of UBC 274 (also reported as LP 5), a recently discovered disrupting OC (Castro-Ginard et al 2020;Piatti 2020), based on 18 members observed with RAVE, GALAH, and Gaia RVS (Fig. 3).…”
Section: Mean Rvsmentioning
confidence: 99%
“…The intrinsic CMD effectively reduces the scatter along the main sequence and highlights a very remarkable equal-mass binary sequence, as analysed by Piatti (2020), but in a larger magnitude range. We notice some possible contaminants at the faint left side of the main sequence (corresponding to apparent magnitudes 17-19), in agreement with the studied recovery statistics where we can expect contamination of 30% (Fig.…”
Section: Cluster Age and Extinctionmentioning
confidence: 87%
“…Later, Piatti (2020) found that the cluster is affected by differential reddening, which ranges from E B−V = 0.1 -0.25. They found log Age = 9.45 ± 0.05 (2.8 ± 0.2 Gyr) provides the best fit to their CMD using the PARSEC isochrones (Bressan et al 2012), with a compromise between the agreement of the turnoff and the red clump.…”
Section: Cluster Age and Extinctionmentioning
confidence: 99%
“…Finally, we would like to mention that extra-tidal stars should have distinct velocities that make it possible for them to escape the cluster. Likewise, they are at different Galactocentric distances than the cluster itself, so that they are differently affected by the Milky Way gravitational field (Piatti 2020;Dinnbier & Kroupa 2020).…”
Section: Discussionmentioning
confidence: 99%